Peran Hygiene Industri dalam Mencegah Penyakit Akibat Kerja: Systematic Literature Review - Hafizah Hafni Siregar; Nabiila Annaufa; Mutiara Ayu Situmorang; Abdurrozaq Hasibuan (Universitas Airlangga, 2026)
Background: Occupational hygiene is a fundamental discipline in workplace health management that safeguards workers from Work-Related Illnesses (WRI) by systematically anticipating, recognizing, and controlling environmental hazards, and evaluating and controlling risk factors in the workplace. Exposure to physical, chemical, biological, ergonomic, and psychosocial hazards can lead to health issues among workers and reduce workplace productivity. Objectives: This study aims to systematically review the role of industrial hygiene in preventing OWDs across various industrial sectors, as well as to identify types of hazards, risk factors, and effective control strategies. Methods: A systematic literature review was conducted using the Google Scholar, Garuda, and SINTA databases with the keywords